Prevalence and genotypes of infectious salmon anaemia virus (ISAV) in returning wild Atlantic salmon (Salmo salar L.) in northern Norway - Madhun, Abdullah Sami; Mæhle, Stig; Wennevik, Vidar; Karlsbakk, Egil (Journal of Fish Diseases, 2019)
publishedVersion